Tolerance of high-yield corn hybrids to early aluminum toxicity - Steiner, Fábio; Silva Melo, Sthela; Kamila Vilas Boas, Jiovana; Mario Zuffo, Alan; Argentel-Martínez, Leandris; González Aguilera, Jorge; Alves, Charline Zaratin (Revista Ciência Agronômica, 2025)
Aluminum (Al3+) inhibits plant growth and limits agricultural production in acidic soils with pH ≤ 5.5. However, high-yielding corn hybrids have distinct degrees of Al3+ tolerance. Exploring this trait may be useful to improve the sustainable use of acidic tropical soils. Fifteen corn hybrids commonly grown in the central-western region of Brazil were assessed for Al3+ stress tolerance during the early plant growth stage. Plants were grown under laboratory conditions with solutions containing 1,000 μmol L–1 Ca2+ (control) or 200 μmol L–1 Al3+ combined with 1,000 μmol L–1 Ca2+ (Al stress). Plant emergence and morphological traits were measured to calculate Al3+ toxicity tolerance indices. The results showed that the corn hybrids AG 8701 PRO4, DKB 390 PRO4, and B2800 VYHR had a greater tolerance to Al3+ toxicity. These findings offer preliminary insights for agricultural cultivation of corn in acidic soil conditions. However, the mechanisms of tolerance to Al3+ toxicity of these corn hybrids still remain unknown. Additionally, the greater stability and tolerance of the corn hybrids AG 8701 PRO4 and DKB 390 PRO4 indicate that these genotypes can be used as genitors in breeding programs to obtain offspring with higher tolerance to Al3+ toxicity. On the other hand, the corn hybrids AG 8088 PRO2, AS 1868 PRO4 and BP 2201 VIP3 are more sensitive to Al3+ toxicity and should not be recommended for cultivation in acidic soils. Therefore, greater attention to soil corrective practices should be given when using these corn hybrids in agricultural areas.